NETWORK PHARMACOLOGY BASED COMPUTATIONAL STUDY TO INVESTIGATE THE POTENTIAL MECHANISM OF SYZYGIUM CARYOPHYLLATUM AGAINST COLON CANCER - PEMMEREDDY, RAMADEVI; MILI, AJAY; BYREGOWDA, BHARATH HAROHALLI; GIRIDHAR, JYOTHI; K, SREEDHARA RANGANATH PAI; MATHEW, ANNA; PAI, VASUDEV; K. S, CHANDRASHEKAR (International Journal of Applied Pharmaceutics, 2025)
Objective: Syzygium caryophyllatum, a traditional medicinal plant from the Myrtaceae family, is rich in potential phytoconstituents. Based on its ethnobotanical uses and documented pharmacological activities, present work was conducted to evaluate the probable mechanism of action of S. caryophyllatum to manage colon cancer by integrating network pharmacology and computational studies. Methods: The plant extract was prepared by Soxhlet extraction method and in vitro screening was performed using Sulforhodamine (SRB) Assay on HT 29 cancer cell lines. We have used super-PRED database, Cytoscape network analyser tool, string database and CytoHubba for performing network analysis for the extract compounds reported in GC-MS analysis. The Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway and DAVID databases were used for gene set enrichment analysis. We have used Schrödinger suite Version 11.4's to perform computational studies. Results: The extract has demonstrated significant in vitro cytotoxic activity (IC50 value is 49.01 µg/ml) and the GC-MS analysis identified seventy-six distinct compounds. The Gene Ontology (GO) and KEGG demonstrated that the shared targets were strongly associated with key processes involved in colon cancer. The current study has identified Estrogen Receptor Alpha (ESR1), Heat Shock Protein 90 Alpha Family Class A Member 1 (HSP90AA1), Mitogen-activated protein kinase 3 (MAP3K), Epidermal Growth Factor Receptor (EGFR) and Signal transducer and activator of transcription 3 (STAT3) proteins as essential targets and 5,7-Dihydroxy-2-undecyl-4H-chromen-4-one, 7a,12-Dihydroindolo[2,3-a] quinolizine, 5-hydroxy-7-methoxy-2-methyl-8-(3-methylbutyl) chromen-4-one as key compounds. Docking studies of the compounds with core proteins completely supplemented their binding affinity and suggested strong interactions at the binding site. Conclusion: These outcomes highlight the multi-target, multi-compound, and multi-pathway approaches of S. caryophyllatum against colon cancer.